Systematic Literature Review (SLR) On Consensus Mechanism In Cyber-Physical System (CPS) For Smart Farm Performance Optimization) - Sri Titi Handayani; Zainal Arifin Hasibuan; Sri Supadmi (Asosiasi Pengelola Jurnal Informatika dan Komputer Indonesia, 2026)
This study aims to analyze the consensus mechanism on the Cyber-Physical System (CPS) to optimize smart farm performance through the Systematic Literature Review (SLR) approach. CPS integration is a fundamental component in smart farms as it allows real-time coordination of sensors, actuators, and computing devices to produce accurate and adaptive farming decisions. However, a dynamic and heterogeneous farming environment demands an efficient, stable, and energy-efficient consensus mechanism so that all nodes in the network can reach a consistent agreement on data or actions. Through SLR on 30 studies, this study found that the consensus mechanism was able to increase sensor synchronization by up to 30%, reduce latency by 27%, decrease water consumption by 19%, increase sensor response by 31%, and improve data security by up to 22%. Several consensus approaches such as average consensus, multi-sensor consensus, secure consensus, edge-based consensus, and fault-tolerant consensus have been proven to improve the accuracy of environmental monitoring, accelerate automatic irrigation response, optimize precision fertilization, and strengthen information search in unstable signal conditions. In addition, consensus in CPS shows a significant role in handling smart farm big data as well as strengthening system resilience to disruptions. However, this study also identified a research gap related to the need for a consensus model that is lighter, adaptive, and in accordance with the characteristics of tropical agriculture such as in Indonesia. These SLR findings provide a direction for the development of more efficient, secure, and sustainable consensus-based CPS for future smart farm implementation.